Bentuk Penyajian Tari Galombang Pada Acara Pesta Perkawinan Di Jorong Koto Kociak Nagari Tujuah Koto Talago Kecamatan Guguak Kabupaten Limapuluh Kota - Rahma Sinta; Herlinda Mansyur (Faculty of Languages and Arts, Universitas Negeri Padang, 2020)
This study aims to describe and reveal the presentation form of Galombang dance at a wedding party in Jorong Koto Kociak Tujuah Koto Talago village, Guguak sub-district, Lima Puluh Kota district. This is a qualitative research using a descriptive analysis method. The object of the research was Galombang dance at a wedding party in Jorong Koto Kociak, Tujuah Koto Talago village, Guguak sub-district, Lima Puluh Kota district and was focused on the form of its presentation. The data were collected through literature review, observation, interview, and documentation. The data analysis was done by using triangulation technique which compared the data from observation to those from interview and documentation data. The results of the study generally show that the Galombang dance is performed in groups by11 dancers. It is performed for eight minutes in front of the bride's house, and it is performed at noon after the procession. Interestingly, the Galombang dance in Jorong Koto Kociak, Tujuah Koto Talag village, is performed by 50 year-old dancers and over (elderly). The presentation form of Galombang Dance at a Wedding Party in Jorong Koto Kociak, Tujuah Koto Talago village, Guguak sub-district, Lima Puluh Kota district is a representational form.The elements of the presentation form of this dance are as follows: (1) The motion of respect, the opening motion, the maagiah kaba motion, the maimbau motion, the basuluah motion, the bagalanggang motion, and silang jentik motion. (2) the Galombang Dance uses a floor pattern of two rows backwards and three carano bearers.(3) The music that accompanies the Galombang dance consists of: bansi, gandang, talempong, and tambourine. (4) The property of Galombang Dance isa carano. (5) The make-up used is pretty makeup. The dancers wear baju kuruang basiba, skirts, scarves, tikuluak kompong and accessories such as necklaces. (6) In addition, the Galombang dance is performed in front of the bride's house.